Chemical Composition and Sensory Quality of Tunisian 'Sayali' Virgin Olive Oils as Affected by Fruit Ripening: Toward an Appropriate Harvesting Time. (6th June 2017) - Nsir, Houda; Taamalli, Amani; Valli, Enrico; Bendini, Alessandra; Gallina Toschi, Tullia; Zarrouk, Mokhtar
Abstract: Herein, the influence of the ripeness of Tunisian Sayali olives on the chemical composition and sensory quality of virgin olive oils have been investigated, with a particular focus on minor metabolites. Towards this end, five samples (S1–S5) were produced from fruits at increasing stages of maturity and then analyzed. Quality indices (free acidity, peroxide value, specific extinction in UV, sensory characteristics) and composition in major (fatty acids) and minor compounds (squalene, pigments, tocopherols, phenolic compounds, volatile compounds), as well as oxidative stability, were evaluated. Significant variations for the most analytical parameters of Sayali samples were demonstrated, highlighting the impact of stage of ripening. In particular, at later stages of ripening a decreased tendency was seen in minor compounds that are able to inhibit lipid oxidation (tocopherols, carotenoids, squalene and polar phenolic compounds) and, as a consequence, in the oxidative stability value. Moreover, a higher intensity of positive sensory notes (fruity, bitter and pungent) characteristic of extra virgin olive oil were found for samples produced with less ripe olives. Finally, a deeper knowledge of the influence of this factor would be helpful to correctly manage the optimal fruit harvesting time for producers for this variety and to improve the marketing of extra virgin olive oils by using a promising secondary variety (with a high oxidative stability and an interesting fatty acid composition).